TUTURAN ILOKUSI JENIS EKSPRESIF DALAM NOVEL AYAHKU BUKAN PEMBOHONG KARYA TERE LIYE - Sari, Riski Monno; Ecca, Suleha; Saifullah; Hanafi, Muhammad (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Understanding expressive illocutionary speech increases the ability to feel and understand the feelings of others, helping to increase empathy and interpersonal support. Overall, a good understanding of expressive illocutionary speech is an important aspect in building effective communication skills and maintaining healthy social and emotional relationships. The importance of understanding expressive illocutionary speech lies in the ability to strengthen interpersonal relationships and prevent miscommunication. In this research, the researcher focuses on expressive illocutionary speech acts with the aim of: (1) Analyzing the function of expressive speech acts in the novel "Ayahku Bukan Pembohong" by Tere Liye, (2) Knowing the contribution of expressive speech act analysis to Indonesian language learning in high school. This research uses a descriptive qualitative method with data in the form of all character dialogue containing expressive forms of speech, collected using reading and note-taking techniques. From the results of data analysis, expressive speech forms were found with the function of praising, the function of complaining, the function of criticizing, the function of thanking, and the function of scolding.